Do burden familiar... à experiência de cuidar: qual o modelo teórico mais adequado para a compreensão da prestação de cuidados informais ao doente esquizofrénico? - Luís Campos (2005)
Desinstitutionalization movement led a great percentage of chronic mental patients being integrated in community. Consequently, familiar burden becomes a central object of concern of scientific community, especially after forties. However, a clear definition of the burden on the family is not consensual in the literature. Furthermore, there is no a standardized instrument that could be consensually accepted by international community as an adequate tool to evaluate it. In this way, this paper aims to contribute with a literature analysis of this issue in order to design an heuristic theoretical model that support further researches in this domain.